A comparative study of the determinants of future plans and expectations of business students. Issue 3 (3rd April 2018) - Black, Gregory S.; Schofield, April L.
ABSTRACT: Current university juniors and seniors have plans and expectations for after they graduate. In an effort to better understand these plans and expectations, the authors assessed a sample of 334 university students enrolled in business classes. The study examined the impact of three categories of independent variables—family influences, demographic influences, and academic influences—on the dependent variables of student degree aspirations, career aspirations, and expected salaries. Determinant variables with the most consistent influences on these dependent variables include birth order and parents' income (family influences); age and ethnicity (demographic influences); and grade point average, college entrance exam scores, and academic major (academic influences).